Drying time of plaster within in-fill plasterboard walls and evaporation theory for water within gypsum: methodology, numerical simulation and application - Shuang-Xi Zhou; Jian-Xin Li; Shu-Feng Bao; Yang Ding; Yong-Qi Wei; An-Ming She; Zhen-Zhen Guo; Jing-Liang Dong (Journal of Asian Architecture and Building Engineering, 2025)
The desulphurisation-gypsum-filling-wall (DSG-FW) formed by pouring into plasterboard partitions with desulphurisation gypsum slurry can utilise low-quality desulphurisation gypsum and also improve the acoustic insulation issues arising from the use of hollow partitions. The construction schedule of this wall is unable to be controlled because the moisture transfer characteristics in DSG-FW are unclear. Therefore, it is important to determine the drying time and the moisture-transfer behaviour during the construction process. By using different thicknesses of gypsum samples, adding different amounts of perlite and adjusting the relative humidity, whether the gypsum board is covered, the drying and evaporating process of gypsum was compared and analysed. The evaporative characteristics of the desulphurisation gypsum core wall at different relative humidities were determined through experiments. In addition, an evaporation model was introduced for simplification and verification. The experimental results show that the drying of gypsum is correlated with relative humidity and gypsum thickness: the higher the relative humidity, the lower the evaporation rate; the thicker the gypsum, the longer the drying time; perlite and gypsum board have no effect on gypsum drying. The rate of evaporation of DSG-FW increases non-linearly with the decrease in relative humidity under which the DSG-FW is conditioned; the simplified Hertz-Knudsen-Langmuir (HKL-S) model can only be used to predict the evaporation behaviour within the higher relative humidity range (more than 55% RH), while the simplified statistical rate theory (SRT-S) model was verified as being able to predict the rate of evaporation across almost the whole relative humidity range. The SRT-S model can be used to predict and control the construction of DSG-FW in actual engineering work.